2013
DOI: 10.1352/1944.7558.118.6.419
|View full text |Cite
|
Sign up to set email alerts
|

A Multimethod Assessment of Anxiety and Problem Behavior in Children With Autism Spectrum Disorders and Intellectual Disability

Abstract: Despite the increased risk for anxiety disorders in children with autism spectrum disorders (ASD), there is a lack of research on the assessment and treatment of anxiety in this population, particularly for those with an intellectual disability (ID). The present study evaluated a multimethod strategy for the assessment of anxiety and problem behavior in three children with ASD and ID. Anxiety was operationally defined using: (1) behavioral data from anxious behaviors, (2) affective/contextual data from parent-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 51 publications
1
24
0
Order By: Relevance
“…Videos were coded for anxiety and problem behaviors. Results indicated greater mean heart rate and lower mean respiratory sinus arrhythmia during the high versus low anxiety context for two of the three children [Moskowitz et al, ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Videos were coded for anxiety and problem behaviors. Results indicated greater mean heart rate and lower mean respiratory sinus arrhythmia during the high versus low anxiety context for two of the three children [Moskowitz et al, ].…”
Section: Resultsmentioning
confidence: 99%
“…Across these studies, a pattern of decreased heart rate seems to emerge for those with autism and anxiety [Guy et al, ; Hollocks et al, ; Kushki et al, ; Mikita et al, ]. Similarly, respiratory sinus arrhythmia may also demonstrate a negative relation with anxiety [Guy et al, ; Moskowitz et al, ]. Some research counters both of these findings; however, demonstrating the opposite pattern—elevated heart rate [Moskowitz et al, ]—or no link at all [Kushki et al, ].…”
Section: Resultsmentioning
confidence: 99%
“…Future research might also better control for the possibility that the individuals studied did not experience situational anxiety in response to the investigator-identified “stressors”. In a single-subject study of three children with autism, Moskowitz et al (2013) examined cardiac responses to anxiety-provoking contexts that were idiosyncratic to that child per parental report (e.g., singing happy birthday, making left turns in the car). In the idiosyncratic high-anxiety contexts the children exhibited significant behavioral evidence of anxiety, accompanied by elevated heart rate and reduced vagal tone, supporting a physiological component of the anxiety response.…”
Section: Behavioral and Genetic Correlates Of Cardiac Activity: Withimentioning
confidence: 99%
“…For example, many individuals with ASD demonstrate an altered physiological stress response to social stimuli; some children with ASD have a heightened response, and others a blunted response to social stimuli (Corbett et al 2012). Several studies have demonstrated correlations between RSA and parent- and self-reported anxiety symptoms in ASD (Guy et al 2014; Kushki et al 2014), as well as operationalized anxious behaviors in observational studies of attachment in children with ASD (Moskowitz et al 2013), indicating that co-occurring conditions may play a prominent role in physiologic variability within ASD. The increasing nuance needed to understand and navigate the social world with the onset of adolescence likely creates a significant challenge to ASD adolescents.…”
Section: Introductionmentioning
confidence: 99%